Metode Pembelajaran “Make A Match” Dan Pengaruhnya Terhadap Hasil Belajar IPA - Rina Hidayati Pratiwi (Florea : Jurnal Biologi dan Pembelajarannya, 2018)
Almost of unspecifically studying methods have been applied teacher for teaching activities. That methods have effected unefficiency for knowledge transferring to student. That is the reason how we need studying methods that efficient, creative and innovative. The purpose of this study is for knowing the studying methods  “Make A Match” and how the impact to result study specifically for natural science. We use purpose sampling technics to definite research class and simple random sampling to definite part of sample of each class. The average score of experiment class are higher than control class. The different of both class is three point with normal distribution for each class and from homogeneity test showed that F hit = 1,163. Both of them have homogeneous varians. The average point of experiment class are higher than control class too. T-test showed  t hit > t table (3,614 > 1,69). Thus, the studying methods  “Make a Match” could raised the study results better than conventional methods. As the result, the quality of education can be more improved agree with contain and the purpose of studying in the school.